25 years post‐Calman: the state of men's health in the UK. Issue 4 (31st July 2017) - Baker, Peter
Abstract : 25 years have passed since the then Chief Medical Officer, Sir Kenneth Calman, included men's health as a 'special topic' in his annual public health report.1 Peter Baker reflects on what has been achieved in the men's health field during this time and what issues remain in need of attention.